ANALISIS UNJUK KERJA ANGKUTAN ANTAR KOTA DALAM PROPINSI RUTE PALU - POSO - Alhadar, Ali (MEKTEK, 2005)
The aim of this research is to evaluation of performance intercities public transportation on route of Palu â€“ Poso Central Sulawesi base on travel time, operation speed, number of passenger, load factor, vehicle operation cost and transport income. The result of this research show thatÂ  operation of intercities transport still eligible base on the speed of operation and amount of vehicle operation cost on the income of the operator of intercities transport, althought benefit of the operator is very law.